Different Families of Retrotransposons and DNA Transposons Are Actively Transcribed and May Have Transposed Recently in Physcomitrium (Physcomitrella) patens - Vendrell-Mir, Pol; López-Obando, Mauricio; Nogué, Fabien; Casacuberta, Josep M. (Frontiers in Plant Science, 2020)
Similarly to other plant genomes of similar size, more than half of the genome of P. patens is covered by Transposable Elements (TEs). However, the composition and distribution of P. patens TEs is quite peculiar, with Long Terminal Repeat (LTR)-retrotransposons, which form patches of TE-rich regions interleaved with gene-rich regions, accounting for the vast majority of the TE space. We have already shown that RLG1, the most abundant TE in P. patens, is expressed in non-stressed protonema tissue. Here we present a non-targeted analysis of the TE expression based on RNA-Seq data and confirmed by qRT-PCR analyses that shows that, at least four LTR-RTs (RLG1, RLG2, RLC4 and tRLC5) and one DNA transposon (PpTc2) are expressed in P. patens. These TEs are expressed during development or under stresses that P. patens frequently faces, such as dehydratation/rehydratation stresses, suggesting that TEs have ample possibilities to transpose during P. patens life cycle. Indeed, an analysis of the TE polymorphisms among four different P. patens accessions shows that different TE families have recently transposed in this species and have generated genetic variability that may have phenotypic consequences, as a fraction of the TE polymorphisms are within or close to genes. Among the transcribed and mobile TEs, tRLC5 is particularly interesting as it concentrates in a single position per chromosome that could coincide with the centromere, and its expression is specifically induced in young sporophyte, where meiosis takes place.